Tinjauan Hukum Islam Terhadap Jasa Titip pada Praktik Jual Beli Tiket Konser di Platform Twitter - Tri, Meliyana Eka Putri; Nurhayati, Agustina; Nur Kholidah, Susi (Universitas Wahid Hasyim Semarang, 2025)
The transformation of information technology in the digital era has revolutionized trade, with buying and selling now shifting to online platforms such as Twitter. One innovation that has emerged is the